Transforming African food systems through bioscience - International Livestock Research Institute (International Livestock Research Institute, 2020)
Watch a virtual tour of ILRI's world-class research facilities in Nairobi, Kenya, which host researchers from more than 10 international institutions who are using bioscience to improve food systems in Africa. This video was part of the United Nations Food Systems Summit (UNFSS) Voices of Food Systems Live: 24-Hour Global Relay Conversation on 16 Oct 2020, which was hosted by Kanayo Nwanze, a UNFSS champion and the CGIAR special representative to the UNFSS, on 'Virtual tours of the coolest African food research centres you never knew about.'